Aplikasi Model Spatial Autoregressive untuk Analisis Prevalensi Balita Underweight di Jawa Tengah Tahun 2021 - Alwanti, Natasya; Berliana, Sarni Maniar; Ayuningtyas, Agian Dila; Simbolon, Rosarina Debesti Tirdvalen; Nafiis, Faried Akbar; Pradiptha, I Gede Nyoman Setya; Rangkuti, Suifatiha (Politeknik Statistika STIS, 2023)
Underweight is a form of nutritional disorder caused by an imbalance between the body's needs and nutrient intake. Underweight is more vulnerable to children under the age of five. Central Java is one of the provinces that has the highest prevalence of underweight children among other provinces on the island of Java. This study aims to determine the factors that influence the prevalence of underweight in Central Java in 2021 by considering spatial effects using data from the Central Java Health Service in 2021, the Central Java BPS in 2021, and the Central Java Data Portal in 2021. The model used in this study this is a spatial autoregressive model (SAR). The SAR model obtained shows that the percentage of infants with low birth weight, the percentage of children with complete immunization, the percentage of antenatal care visits according to program recommendations and the percentage of children under five weighed significantly affect the prevalence of underweight.